2021
DOI: 10.3390/rs13214470
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Coral Reefs with Multispectral Satellites: A Review of Recent Papers

Abstract: Coral reefs are an essential source of marine biodiversity, but they are declining at an alarming rate under the combined effects of global change and human pressure. A precise mapping of coral reef habitat with high spatial and time resolutions has become a necessary step for monitoring their health and evolution. This mapping can be achieved remotely thanks to satellite imagery coupled with machine-learning algorithms. In this paper, we review the different satellites used in recent literature, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 251 publications
(282 reference statements)
0
7
0
Order By: Relevance
“…Apart from DSF, several ACs processor tools have their mechanisms for adjusting for inland water bodies, but a comparative analysis indicated that six such tools showed high levels of uncertainties in the water-leaving reflectance estimation (Warren et al, 2019). Similar uncertainty has been found for atmospheric correctness computed for oceans when mapping coral reefs (Nguyen et al, 2021).…”
Section: Atmospheric Correctionmentioning
confidence: 81%
See 1 more Smart Citation
“…Apart from DSF, several ACs processor tools have their mechanisms for adjusting for inland water bodies, but a comparative analysis indicated that six such tools showed high levels of uncertainties in the water-leaving reflectance estimation (Warren et al, 2019). Similar uncertainty has been found for atmospheric correctness computed for oceans when mapping coral reefs (Nguyen et al, 2021).…”
Section: Atmospheric Correctionmentioning
confidence: 81%
“…Change detection using MSI is particularly important for applications related to environmental monitoring, for example, surface water and flood detection (Albertini et al, 2022), shoreline indicators (McAllister et al, 2022), coral reefs mapping (Nguyen et al, 2021), and biodiversity monitoring (Kuenzer et al, 2014; Schulte to Bühne & Pettorelli, 2018). The latter pertains to specific regions, such as forests (Kacic & Kuenzer, 2022), grasslands (Jackson et al, 2022).…”
Section: Multimodal Data Miningmentioning
confidence: 99%
“…The MLC method has been frequently used and regarded as a standard approach in remote sensing image processing [39,40]. This approach assumes that the probability density function follows the normal distribution [41].…”
Section: Classification Maximum Likelihood (Mlc)mentioning
confidence: 99%
“…In particular, any in situ measurements of coral reefs are challenging for the remote Spratly Islands [11,18], which contain the elements of the present political situation. Currently, in situ measurements for acquiring bathymetric maps in remote coral reefs can be replaced using satellite-derived bathymetry (SDB) [19][20][21][22].…”
Section: Of 19mentioning
confidence: 99%